Estimation of combining ability and heterosis in bottle gourd (Bangladesh Journal of Botany, 2025)
To develop high yielding and early maturing hybrid, an experiment was conducted to assess the combining ability and heterosis in bottle gourd. This study utilized 30 genotypes, comprising 7 diverse parental lines (HAJARI, BG714, BG717, BG719, BG720, BG722, and BG725), 21 F1 hybrids generated through a 7 × 7 half-diallel crossing method, and two commercial checks (Diana and Moyna). The experimental design followed a Randomized Complete Block Design (RCBD) with three replications. Analysis of variance revealed significant differences among parents, hybrids, and their interactions across all 11 evaluated traits. Combining ability analysis showed that both general combining ability (GCA) and specific combining ability (SCA) variances were highly significant. GCA/SCA ratios for key traits such as yield per plant (0.33) and harvest duration (0.30) were below 1, indicating the predominance of non-additive gene action and confirming the suitability of hybrid breeding for trait improvement. BG714 exhibited superior GCA effects for both early harvesting and higher yield. Crosses BG714 × BG722 and BG714 × BG717 showed the highest positive SCA and heterosis for yield per plant and fruit number. HAJARI × BG719 and BG719 × BG722 displayed significant standard heterosis compared to both checks for yield and earliness. These findings underscore the genetic potential of these hybrids for commercial cultivation and highlight the value of hybrid breeding in bottle gourd for enhancing productivity, earliness, and adaptability under diverse growing conditions.Bangladesh J. Bot. 54(3): 601-609, 2025 (September)